Non-labile plant C contributes to long-lasting macroaggregation of an Oxisol - Martins, Márcio R. [UNESP]; Angers, Denis A.; Corá, José E. [UNESP] (Elsevier, 2013)
Decomposition of plant material influences soil aggregation dynamics in ways that are still poorly understood, especially for Oxisols, in which oxides are believed to play a dominant role. In an incubation experiment, we investigated (i) the effect of plant material addition from selected monocot and dicot species on soil organic C (SOC), carbohydrate composition, fungal and total microbial biomass, and aggregation of an Oxisol; and (ii) the relationship among these properties and C mineralization patterns. The experiment was carried out at 25 °C for 180 d after addition of 11 plant materials (4 g C kg-1 soil) and a control (no plant material added). Mineralization of C during the incubation was described considering two pools of C (labile and non-labile) using a first-order plus linear fitting. Compared to the control, corn materials showed larger pentose input, greater mineralization rates for the non-labile C pool (k), greater soil pentose content (xylose + arabinose) and larger mean weight diameter of soil water-stable aggregates at 180 d of incubation. These effects were independent of changes in SOC content, suggesting that total C accrual and macroaggregation may be decoupled processes in this Oxisol. Our results support the hypothesis that the non-labile plant C pool contributes to the long-lasting stability of macroaggregates of this Oxisol and that this effect is mediated by plant and soil pentoses. We propose that plant pentose content and the decomposition rate of the slow pool (k) are useful parameters for the prediction of plant effects on aggregation dynamics of Oxisols and the selection of soil conservation practices. © 2012.
Keywords: Aggregate; Carbohydrates; Carbon pools; Mineralization model; Non-labile carbon; Oxisol; Aggregation dynamics; C mineralization; Carbon pool; Conservation practices; Decomposition rate; First-order; Linear fitting; Long lasting; Macroaggregates; Mean weight diameter; Microbial biomass; Oxisols; Plant material; Soil aggregation; Soil organic C; Aggregates; Carbon; Dynamics; Experiments; Forestry; Mineralogy; Organic carbon; Soil conservation; Soil moisture; Lakes; biomass; biomineralization; carbohydrate; decomposition; macroaggregate; soil aggregate; soil carbon; soil conservation; soil microorganism; soil organic matter; Dicotyledoneae; Zea mays